Strategies of International Advertising: the Peculiarity of Selection and Application - Žukauskas, Pranas (Ekonomika, 1997)
The article discusses the important problem of contemporary international marketing-advertising abroad. The current debate among marketers is the effectiveness of standardized versus modified advertising for culturally and legitimately varied markets. Both concepts are presented in the article including their advantages and imperfections. The conclusion is made that the most logical and flexible strategy of international advertising is based upon the mixed advertising standpoint. According to this conception, world markets after special marketing research - are divided into larger or smaller regions with different needs for advertising strategies. Six tactics for the adaptation of international advertising messages, depending upon the level of the product’s adaptation to foreign consumers’ needs, are presented in the article.